β2-adrenergics in hypoxia desensitize receptors but blunt inhibition of reabsorption in rat lungs - Baloğlu, Emel; Reingruber, Thomas; Bärtsch, Peter; Mairbäurl, Heimo (American journal of respiratory cell and molecular biology, 2011)
Alveolar edema and decreased inspired Po2 decrease the oxygen supply to alveolar epithelia, impairing β2-adrenergic receptor (β2AR) signaling and alveolar reabsorption. β2AR agonists potently stimulate alveolar reabsorption. Thus, hypoxia impairs a major defense mechanism that provides protection from alveolar edema. Because in vivo data on the combined effects of prolonged hypoxia and β2AR agonist treatment on β2AR signaling are sparse, we tested whether in vivo hypoxia augments the inactivation of β2AR during prolonged stimulation. Rats were exposed to normoxia (N) and hypoxia (8% O2; H), and were also treated with terbutaline (T; 2.5 mg/kg, intraperitoneal, twice daily) or saline (S) for 4 days. β2AR signaling was studied in alveolar epithelial (ATII) cells and in whole-lung tissue from treated rats. The terbutaline-stimulated formation of cyclic adenosine monophosphate was decreased by approximately 40% in whole lung and in ATII cells of NT, HS, and HT. The effects were not additive. The β2AR number was increased in HS, but decreased in NT and HT. Treatment increased the G-protein-coupled receptor kinase 2 protein in the plasma membranes of ATII cells, but did not affect G proteins. In vivo hypoxia significantly decreased total and amiloride-sensitive alveolar fluid reabsorption, which was prevented by acute alveolar treatment and 4 days of systemic terbutaline treatment. The αENaC (subunit of epithelial Na channels) protein in plasma membranes was increased in HT, without effects on mRNA. These results indicate that prolonged alveolar hypoxia and treatment with terbutaline impaired β2AR signaling in alveolar epithelia and in whole lungs, and this signaling was not further impaired by hypoxia. Despite impaired β2AR signaling, treatment with terbutaline for 4 days prevented the inhibition of alveolar reabsorption caused by in vivo hypoxia.